Molecular detection of Aeromonas hydrophila from frozen fish; a food quality and safety concern - Kadum, Hana; Isa, Shu’aibu; Muhammad, Khairiyya (Elite Scientific Publications, 2024)
Aeromonas hydrophila is a pathogenic bacterium affecting fish that when ingested by humans, induces gastroenteritis. This research aimed to evaluate the occurrence of A. hydrophila from five different frozen fish brands labeled A-E marketed from five different stalls labeled 1-5, in Kano metropolis, Kano State, Nigeria. The first three brands A, B, and C were local brands while C and D were of foreign origin. A total of 500 samples, 100 from each brand were purchased from retail stalls as frozen fish and processed for the isolation and biochemical identification of A. hydrophila. Polymerase chain reaction (PCR) using specific ahh1 primer was employed to confirm the identity of A. hydrophila. Overall, 48% (n=240) of the samples were positive for A. hydrophila with incidences of 12% (n=60), 10% (n=50), 14% (n=70), 6% (n=30) and 6% (n=30) for A, B, C, D, and E brands respectively. Out of 240 samples, 20% (n=48), 21.25% (n=51), 19.17% (n=46), 19.58% (n=47) and 20% (n=48) were detected from stalls 1, 2, 3, 4 and 5 respectively. The PCR detection reveals the presence of ahh1 gene having 130 bp size. Presence of A. hydrophila in fish and fish products is a potential for spoilage and infection due to the organism.